1985
DOI: 10.1002/j.2050-0416.1985.tb04326.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Infraalyzer 400 for the Analysis of Barley and Malt

Abstract: A collaborative study is described of the use of infra-red reflectance for the evaluation of the analytical characteristics of barley and malt. Transfer of centrally-prepared calibrations to other reflectance machines was found to be possible for moisture content and protein content in barley and malt but not for malt extract or malt modification. The examination of infra-red reflectance results, obtained at different wavelengths, by step-wise ascending regression rather than step-wise descending regres sion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…A high negative correlation coefficient in both barley and malt hordein was evident (data not shown). This wavelength was also reported by a number of other researchers in both filter and scanning studies including 6,33 when using for filter instruments. In addition, Williams et al 37 reported 1680 nm in calibrations for aromatic amino acids including phenylalanine and tyrosine in barley.…”
Section: Vsximr 7tigxvesupporting
confidence: 79%
“…A high negative correlation coefficient in both barley and malt hordein was evident (data not shown). This wavelength was also reported by a number of other researchers in both filter and scanning studies including 6,33 when using for filter instruments. In addition, Williams et al 37 reported 1680 nm in calibrations for aromatic amino acids including phenylalanine and tyrosine in barley.…”
Section: Vsximr 7tigxvesupporting
confidence: 79%